The impact of building-renovation program on the city’s environment - Lunyakov Mikhail Alexandrovich; Kirpichenkov Andrey Andreevich (E3S Web of Conferences, 2023)
Implementation of the residential renovation program, which is currently underway in the city of Moscow, as well as in other cities of the Russian Federation, helps to create comfortable and safe living conditions for citizens. In addition, one of the most important tasks of this program is the integrated development of urban areas: development of public spaces, landscaping of districts, organization of parks and recreation areas. These aspects help to create more favorable living conditions and also have a positive impact on the environmental component of the area. As renovation of residential buildings is a combination of renovation or modernization of existing buildings, more attention is being paid to the energy efficiency of buildings, as well as their impact on the environment. For example, modernizing the engineering systems, improving the thermal conductivity of the building envelope and other aspects can reduce greenhouse gas emissions; reduce energy consumption and so on. Thus, the implementation of the housing renovation program, due to its massive scale, has a favorable impact on the environmental condition of the city and its districts.